Coordinated Control of Networked AC/DC Microgrids With Adaptive Virtual Inertia and Governor-Gain for Stability Enhancement - Zhang, Yi; Sun, Qiuye; Zhou, Jianguo; Li, Linjuan; Wang, Panfeng; Guerrero, Josep M. (IEEE transactions on energy conversion, 2021)
This article proposes an adaptive coordinated control strategy for the networked AC/DC microgrids (MGs) to enhance the frequency and dc voltage stability of the system while keeping proper power sharing. First, a control strategy based on the synchronverter and virtual dc machine (VDCM) for the converters connecting the AC and DC MGs is proposed, which is consisted of an adaptive virtual governor and an adaptive virtual inertia regulator besides the power sharing controller. Following, in order to enhance the system stability performance, the parameter design approach of the adaptive virtual inertia and virtual governor-gain is proposed accordingly, in which the adaptive virtual inertia and virtual governor-gain are comprehensively determined by the frequency and/or dc voltage, virtual rotor speed, and rate of change of the frequency (ROCOF) and/or dc voltage (ROCOV). After that, the small-signal stability analysis of the networked AC/DC MGs with the proposed control strategy is investigated to guide the design and selection of control parameters. Finally, simulation and experimental results demonstrate that the proposed method improves the frequency/dc voltage nadir and dynamic performance of the system.